Meals, identity and othering in Mark 14:12–26 - Hombana, Mphumezi; Maqajana, Thembelani (Verbum et ecclesia, 2025)
This article investigates the concept of ‘othering’ in the context of the Markan Jesus’ Last Meal (Mk 14:12–26), examining how this pivotal event in the gospel contributes to the discourse on social constructs and identity formation in African societies. Meals hold significant cultural and social value in Africa, where they play a central role in community cohesion and identity definition. However, in diverse and complex societies, such as those found among South Africa’s black Indigenous groupings, meals also bring to the fore issues of identity and belonging, often complicated by the dynamics of othering. The Markan narrative, with its depiction of Jesus’ Last Supper, offers a profound lens through which to interrogate these issues. By analysing the Last Meal in Mark 14, this article explores how this event speaks to the challenges of identity formation and social cohesion in contemporary South African contexts in which divisions, discrimination, social unrest and instability are prevalent. It argues that the Last Meal understood through the framework of othering provides critical insights into the potential of communal meals to either reinforce divisions or foster reconciliation and unity in fractured societies, such as South African communities.Intradisciplinary and/or interdisciplinary implicationsThe concept of ‘othering’ refers to the process by which individuals or groups are categorised as fundamentally different from and often inferior to the dominant group. This process is central to the construction of social identities and the maintenance of power dynamics within societies.